The 2020 glacial lake outburst flood at Jinwuco, Tibet: causes, impacts, and implications for hazard and risk assessment - G. Zheng; M. Mergili; A. Emmer; S. Allen; A. Bao; H. Guo; M. Stoffel (The Cryosphere, 2021)
We analyze and reconstruct a recent glacial lake outburst flood (GLOF) process chain on 26 June 2020, involving the moraine-dammed proglacial lake – Jinwuco (30.356∘ N, 93.631∘ E) in eastern Nyainqentanglha, Tibet, China. Satellite images reveal that from 1965 to 2020, the surface area of Jinwuco has expanded by 0.2 km2 (+56 %) to 0.56 km2 and subsequently decreased to 0.26 km2 (−54 %) after the GLOF. Estimates based on topographic reconstruction and sets of published empirical relationships indicate that the GLOF had a volume of 10 million cubic meters, an average breach time of 0.62 h, and an average peak discharge of 5602 m3/s at the dam. Based on pre- and post-event high-resolution satellite scenes, we identified a large debris landslide originating from western lateral moraine that was most likely triggered by extremely heavy, south-Asian-monsoon-associated rainfall in June 2020. We back-calculate part of the GLOF process chain, using the GIS-based open-source numerical simulation tool r.avaflow. Two scenarios are considered, assuming a debris-landslide-induced impact wave with overtopping and resulting retrogressive erosion of the moraine dam (Scenario A), as well as retrogressive erosion without a major impact wave (Scenario B). Both scenarios are in line with empirically derived ranges of peak discharge and breach time. The breaching process is characterized by a slower onset and a resulting delay in Scenario B compared to Scenario A. Comparison of the simulation results with field evidence points towards Scenario B, with a peak discharge of 4600 m3/s. There were no casualties from this GLOF, but it caused severe destruction of infrastructure (e.g., roads and bridges) and property losses in downstream areas. Given the clear role of continued glacial retreat in destabilizing the adjacent lateral moraine slopes and directly enabling the landslide to deposit into the expanding lake body, the GLOF process chain can be plausibly linked to anthropogenic climate change, while downstream consequences have been ...